Political incorporation in measures of democracy: a missing dimension (and the case of Bolivia). Issue 4 (19th May 2018) - Wolff, Jonas
ABSTRACT: Since President Morales took office in Bolivia in early 2006, the country has undergone a complex political transformation. This profound process of change is, however, hardly reflected in established democracy indices, which by and large paint a picture of institutional continuity. Taking this puzzling observation as a starting point, the article compares qualitative and quantitative assessments of Bolivia's contemporary political regime and argues that existing measures of democracy largely miss one key dimension that is crucial when it comes to analysing (changes in) the quality of democracy: the issue of political incorporation. Specifically, the case of Bolivia shows that democracy indices mostly ignore important changes in terms of descriptive representation, party incorporation, and non-electoral participation. Privileging an individualist conception of liberal democracy, democracy measures downplay the relevance of collective forms of political representation and participation and, hence, the extent to which different social groups are or are not incorporated into the political system. As a result, these measures of democracy mostly do not "count" the recent progress in the political incorporation of important parts of the Bolivian population, which had been largely absent from the country's political institutions despite two decades of continuous democratic rule.